Renewable Energy Technologies and Hybrid Electric Vehicle Challenges - Azidin, Farid Arafat; Hannan, Mahammad Abdul; Mohamed, Azah (2013)
This paper introduces the utilization of selected renewable energy technologies such as solar cell, battery, proton exchange membrane (PEM) fuel cell (FC) and super-capacitors (SCs) in the electrical vehicle industry. Combination of multiple energy resources is imperative to balance the different characteristic of each resource. Concomitantly, the need of an efficient energy management system arises within the industry. Thus, existing system from past and present undergoing research papers are summarized to give a compact overview on the technology and know-how technique to readers.